Evaluation Of The Discipline Of Computer Technology Attendance Fingerprint Of Sports Teachers And All Teachers Who Teach At Public Elementary Schools In The Upper Yellow District Of Southeast Aceh - Zaini Hasan; Anton Purnama (Journal Informatic, Education and Management (JIEM), 2025)
The main objective of this study is to describe the level of discipline of computer technology fingerprint attendance of PE teachers and all teachers who teach at Sekolah Dasar Negeri Kuning Atas and to identify the factors that influence such discipline. This research aims to provide a comprehensive picture of how sports teachers and all teachers who teach at Sekolah Dasar Negeri Kuning Atas carry out their responsibilities in the context of education, as well as to explore the internal and external factors that may influence their discipline, such as personal motivation and support from school management. The research method used is a qualitative approach, with data collection through interviews and observations. This study found that there are several indicators of discipline, including obeying the rules, self-control, and creative attitude. In addition, the factors that influence the discipline of computer technology fingerprint attendance for sports teachers and all teaching teachers include personal motivation, work environment, and support from school management. In the discussion, the author analyzes the findings by referring to the theories of work discipline in education. Fingerprint computer technology attendance for sports teachers and all teachers who teach is very important to create a conducive learning and teaching atmosphere and to achieve better educational goals. Recommendations are given that schools and education offices pay attention to this discipline problem as part of efforts to improve the quality of education in the area. This research is expected to be a reference for policymakers in formulating strategies to improve the discipline of computer technology fingerprint attendance for sports teachers and all teachers who teach in elementary schools.